Swarm-Oriented Programming of Distributed Robot Networks. - Pinciroli, Carlo; Beltrame, Giovanni (Computer (00189162), 2016)
One challenge of programming soon-to-be-common large robotic teams is the definition of programming primitives that generate reusable and predictable behaviors. A new language construct allows developers to categorize robots using custom conditions and assign tasks to the groups created. The web extra at https://youtu.be/ddHXIef3nDo offers a real-life demonstration of a robot swarm programmed using Buzz, an extension language with dynamic typing.